Recycling of sugar industry wastewater for single-cell protein production with supplemental carotenoids - Saejung, Chewapat (Environmental technology, 2020)
The bioconversion of sugar-industry wastewater to value-added products is a prominent topic in biotechnology. This work cultured a carotenoid-producing photosynthetic bacterium, Rhodopseudomonas faecalis, in a photo-bioreactor containing different wastewater from wastewater treatment ponds of a Thai sugar company. The cultivated R. faecalis produced single cell protein (SCP) with supplemental carotenoids. The cultivation boosted the growth and dehydrogenase activity of R. faecalis from all wastewater sources, while significantly reducing the total sugar concentration. The cellular protein concentration and carotenoid production of R. faecalis was maximised in wastewater collected from anaerobic pond and secondary mechanically aerated pond, respectively. At the end of the cultivation, the chemical oxygen demand was reduced by 80% and the protein content in the dry biomass exceeded 50%, within the acceptable ranges of SCP production. The biomass contained all essential amino acids and the leucine and lysine proportions were above the SCP guideline values. This study reveals that sugar-industry wastewater can be recycled in SCP production with supplemental carotenoids. The SCP is a potential commercial product for the sugar industry